PsEND1 Is a Key Player in Pea Pollen Development Through the Modulation of Redox Homeostasis - Hamza, Rim; Roque, Edelín; Gómez-Mena, Concepción; Madueño, Francisco; Beltrán, José Pío; Cañas, Luis A. (Frontiers in Plant Science, 2021)
Redox homeostasis has been linked to proper anther and pollen development. Accordingly, plant cells have developed several Reactive Oxygen Species (ROS)-scavenging mechanisms to maintain the redox balance. Hemopexins constitute one of these mechanisms preventing heme-associated oxidative stress in animals, fungi, and plants. Pisum sativum ENDOTHECIUM 1 (PsEND1) is a pea anther-specific gene that encodes a protein containing four hemopexin domains. We report the functional characterization of PsEND1 and the identification in its promoter region of cis-regulatory elements that are essential for the specific expression in anthers. PsEND1 promoter deletion analysis revealed that a putative CArG-like regulatory motif is necessary to confer promoter activity in developing anthers. Our data suggest that PsEND1 might be a hemopexin regulated by a MADS-box protein. PsEND1 gene silencing in pea, and its overexpression in heterologous systems, result in similar defects in the anthers consisting of precocious tapetum degradation and the impairment of pollen development. Such alterations were associated to the production of superoxide anion and altered activity of ROS-scavenging enzymes. Our findings demonstrate that PsEND1 is essential for pollen development by modulating ROS levels during the differentiation of the anther tissues surrounding the microsporocytes.